2002
DOI: 10.1046/j.1439-0442.2002.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytometric Evaluation of Peripheral Blood Lymphocytes in Dogs with Lymphoma during Chemotherapy

Abstract: Twenty dogs with clinically diagnosed multicentric lymphoma were evaluated for percentages of peripheral blood lymphocyte subpopulations. Cytometric analysis was performed before and during chemotherapy. The results were compared to those obtained from a control group of healthy dogs. The percentages of CD5+, CD4+ and CD8+ cells were markedly decreased and CD21-like+ cells markedly increased in dogs with lymphoma in comparison with the control group. During the course of chemotherapy these values returned to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
2
5
2
2
Order By: Relevance
“…O 'Neill et al (2009) The results of the present study show that the percentages of the subpopulations of CD4 + and CD8 + T-cells were not altered by chemotherapy and are in agreement with the results of other studies in dogs with lymphoma and multicentric lymphoma (Winnicka et al, 2002;Mitchell et al, 2012) and in dogs with osteosarcoma (Walter et al, 2006). Gauthier et al (2005) observed that chemotherapy caused a significant reduction in the absolute value of the majority of lymphocyte subpopulations of dogs with lymphoma.…”
Section: Cd4supporting
confidence: 92%
See 3 more Smart Citations
“…O 'Neill et al (2009) The results of the present study show that the percentages of the subpopulations of CD4 + and CD8 + T-cells were not altered by chemotherapy and are in agreement with the results of other studies in dogs with lymphoma and multicentric lymphoma (Winnicka et al, 2002;Mitchell et al, 2012) and in dogs with osteosarcoma (Walter et al, 2006). Gauthier et al (2005) observed that chemotherapy caused a significant reduction in the absolute value of the majority of lymphocyte subpopulations of dogs with lymphoma.…”
Section: Cd4supporting
confidence: 92%
“…Similar results have been previously reported by O'Neill et al (2009), who analysed dogs with various types of neoplasia (sarcoma, carcinoma, lymphoma and mastocytoma) and by Mitchell et al (2012) in dogs with type B lymphoma. On the other hand, other studies (Winnicka et al, 2002;Walter et al, 2006) have reported significant differences between healthy and neoplastic dogs and have attributed such differences to factors related to the tumours, suggesting that these tumours can be suppressive; however, no information on the type of suppression was provided (Winnicka et al, 2002). Some factors could have influenced this analysis and may explain some of the discrepancies in the results.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Bei den meisten mediastinalen und epidermotropen Lymphomen handelt es sich um T-ZellLymphome (MOORE et al, 1994;VAIL et al, 1996;RUSLANDER et al, 1997 (DUNCAN & PRASSE, 1979;CHUN et al, 2007;VAIL & YOUNG, 2007;DICKINSON, 2008 (CHABANNE et al, 2000a;CULMSEE et al, 2001). Diese Immuntypisierung kann sowohl mit Lymphknotenaspiraten als auch mit peripherem Blut durchgeführt werden (WINNICKA et al, 2002;MINISCALCO et al, 2003;GIBSON et al, 2004).…”
Section: Das Mediastinale Lymphom Geht Mit Einer Vergrößerung Mediastunclassified